A 15-Year-Old Boy with Anterior Chest Pain, Progressive Dyspnea, and Subcutaneous Emphysema of the Neck. (1st February 2009) - Scichilone, Nicola; Buttacavoli, Maria; Camarda, Gaetana; Marchese, Margherita; Bellia, Maria; Spatafora, Mario
Abstract : We describe the case of an adolescent who was admitted to the hospital because of sudden occurrence of chest pain, dyspnea and subcutaneous emphysema. On admission, physical examination revealed subcutaneous crepitations in the superior part of the rib cage, and auscultation of the chest showed widespread wheezing. The radiological assessment confirmed the diagnosis of pneumomediastinum and pneumothorax. A follow-up CT scan performed one week after the admission showed almost complete resolution of the radiological alterations. At the following visits, the patient was asymptomatic, but reported to have suffered from frequent episodes of rhinorrea, sneezing, nasal blockage, and sometimes, chest tightness, especially during exposure to pets and/or windy weather. Skin prick testing showed sensitivities to dermatophagoides pteronyssinus and farinae, grass pollen and dog dander. Spirometry documented significant improvement in lung function after short-acting bronchodilator, allowing for the diagnosis of asthma to be made. Although pneumomediastinum may be a complication of various respiratory diseases, including asthma, it has never been reported as the first presentation of underlying bronchial asthma. Herein, the physiopathological mechanisms, the diagnostic procedures and treatment of pneumomediastinum in asthma are discussed. We suggest that the diagnosis of asthma should be considered in the differential diagnosis of pneumomediastinum in adolescence.